Polemika na temat przydatności podziału na czynności kauzalne i abstrakcyjne – wybrane zagadnienia - Nowakowski, Tobiasz (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2017)
The author has presented different conception of dualistic divide on causation and non-causation legal actions. The analyses focuses on need to abandon that dualistic divide. The main argument is ambiguity word of causae. Author’s view is based on polish conventional legal actions theory. It professes that each legal action has got constructional and consequential principles, which are sufficient to describe consideration of them.
The polemic of usefulness divide of causation and non-causation legal actions – chosen issues
Keywords: causae; legal action; conventional legal action theory; obligation